The Action Constraints of an Object Increase Distance Estimation in Extrapersonal Space - Josa, Romàn Viçenç; Camus, Thomas; Murday, Vincent; Morgado, Nicolas; Palluel-Germain, Richard; Brunel, Lionel; Brouillet, Denis (Frontiers in Psychology, 2019)
This study investigated the role of action constraints related to an object as regards allocentric distance estimation in extrapersonal space. In two experiments conducted in both real and virtual environments, participants intending to push a trolley had to estimate its distance from a target situated in front of them. The trolley was either empty (i.e., light) or loaded with books (i.e., heavy). The results showed that the estimated distances were larger for the heavy trolley than for the light one, and that the actual distance between the participants and the trolley moderated this effect. This data suggests that the potential mobility of an object used as a reference affects distance estimation in extrapersonal space. According to embodied perception theories, our results show that people perceive space in terms of constraints related to their potential actions.